Pemberian Terapi Benson terhadap Kecemasan Pasien Pre Operasi Fraktur: Case Report - Helen Octavira Wisdaningrum; Dyah Rivani; Suprianto (An-Najat, 2024)
Fracture is a condition where the bone breaks due to trauma, excessive pressure, or conditions that weaken the bone. Treatment for fracture cases is usually surgery. Pre-surgery often causes anxiety in patients, disrupts the healing process and affects quality of life. One way to reduce anxiety levels is with Benson relaxation therapy. This case study aims to determine the effectiveness of providing Benson relaxation therapy on preoperative patient anxiety levels. This study used a case report method with nursing intervention in the form of Benson relaxation therapy which was carried out for 2 days. The results of this study show that after 2 days of Benson relaxation therapy intervention, the patient's anxiety level decreased from a scale of 26 (moderate) to a scale of 20 (mild). Benson relaxation therapy is effective in reducing anxiety in preoperative patients.